Evaluation of the Therapeutic Efficacy of Perceptual Learning Using the Bartimeus Training Program in the Clinic as an Additional Therapy to Glasses or Patching - Maurer, Simon Gustav Arpàd; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2023)
Background The Bartimeus training program (BT) is a perceptual learning task that consists of a drawing assignment performed in 12 sessions of 30 minutes duration. Here we aim to retrospectively assess visual improvement in children who underwent BT and in whom visual acuity had not improved by glasses or patching in relation to patient age and diagnosis.Material and Methods Retrospective chart analysis of patients who had undergone BT at our institution after consent. Visual acuity prior to and following BT was analyzed, as were diagnosis and age at BT.Results Thirteen patients (20 eyes) with a mean age of 7 years (range: 3.9 – 10.75) were included. Overall acuity (LogMar) improved in 75%. Six patients aged 6.5 – 7.5 years had a mean improvement of 1.4 lines. The greatest improvement (5 lines crowding acuity) was seen in a 9-year-old with recent onset amblyopia due to corneal scarring. Two patients aged 6 years with deprivation amblyopia following surgery of a congenital cataract and one 5-year-old with retinitis pigmentosa did not benefit from BT.Conclusions BT is a cheap noninvasive method that may help improve visual outcomes. Further studies with larger numbers are needed to assess optimal indication, timing, and length of treatment.
Keywords: amblyopia in children; Bartimeus Crowding Training; perceptual learning